Effectiveness of Soybean Meal as a Feed Supplement on Gonadal Maturation, Gonadosomatic Index (GSI), Hepatosomatic Index (HSI), and Spawning Success of Female Broodstock Catfish - Vika Maulidiyah; Rizky Kusma Pratiwi; Anissa Aprilia Nurkhasanah; Andi Masriah; Amalia Febryane Adhani Mazaya; Maura Yasmin Dhia; Fajar Maulana Akmal Firdaus (Politeknik Negeri Sambas, 2025)
The increasing demand for catfish (Clarias sp.) consumption necessitates a sustainable supply of broodstock and seed for aquaculture. One of the main constraints in meeting this demand is the low gonadal maturation rate of catfish outside the natural spawning season. Reproductive hormones play a central role in regulating gonadal maturation through the action of estrogen hormones, particularly 17β-estradiol, which stimulates vitellogenesis or the synthesis of vitellogenin (egg yolk), a major component of oocytes. The increase in vitellogenesis and oocyte size is positively correlated with the level of gonadal maturity. Soybean is a natural source of phytoestrogens that function similarly to estrogen and is rich in linoleic acid, which can stimulate the production of 17β-estradiol. This study aimed to determine the effect of soybean flour supplementation in feed on the Gonadal Maturity Level (GML), spawning success, Gonadosomatic Index (GSI), and Hepatosomatic Index (HSI) of female catfish broodstock. The experimental treatments included a control group (without soybean flour), TK 5% (supplementation of 5% soybean flour per kg of feed), and TK 10% (supplementation of 10% soybean flour per kg of feed). The results showed no significant differences among treatments in terms of GML, spawning success, GSI, or HSI of female broodstock. However, a potential increase in GSI was observed with higher soybean flour supplementation, with the highest GSI value recorded at the 10% dosage level.